The Effect of Translation on Multinational Corporations' Internal Performance Evaluation - Gernon, Helen (Journal of International Business Studies, 1983)
This study investigated the effect that FASB No. 8 has had on the internal performance evaluation practices of 70 U.S.-based MNCs. Questionnaire data were gathered and analyzed while additional information was obtained through personal interviews. The results indicated that FASB No. 8 caused changes in corporate managerial reporting policies. Thirty-one participants (44.2 percent) changed to the temporal method of translating financial information for internal reporting purposes. Twenty-seven (38.6 percent) began using an income figure that had been adjusted for translation gains and losses to evaluate foreign subsidiary managers. Forty-six (65.7 percent) stated that financial statements presented in local currency provide better information that U.S. dollar statements for the internal evaluation of foreign operations. The author argues that MNCs need performance evaluation systems that are developed independently of FASB external reporting standards and that advocate a local perspective relative to foreign operating environments.